A look at clinical trial design for new antimicrobials for the adult population. Issue 11 (2nd November 2019) - Bassetti, Matteo; Giacobbe, Daniele Roberto; Peghin, Maddalena; Irani, Paurus
ABSTRACT: Introduction : Antimicrobial resistance poses a substantial threat to global public health since it decreases the probability of effectively treating an infection and increases the risk of morbidity and mortality. Areas covered : In this review, the authors discuss the advantages and disadvantages of classical and novel trial designs for evaluating novel antibiotics for infections due to multidrug-resistant organisms (MDRO). An inductive literature search was performed using different keywords pertinent to the reviewed topics. Expert opinion : The need for active, effective compounds has strengthened regulatory, academic, and industry cooperation, leading to the recent approval of some novel anti-MDRO agents, with other promising compounds being also in the late phase of clinical development. Nonetheless, some important issues regarding the design of clinical trials have gained importance that are peculiar for novel anti-MDRO agents and should be addressed for continuing to guarantee the availability of effective treatments in the future. Very importantly, concerted cooperation with regulatory agencies will always be needed for continuously discussing and refining the acceptable level of evidence to be pursued through non-conventional and/or innovative trial designs or development strategies. Failure to do so would seriously pose the risk of perpetuating the unmet need for effective anti-MDRO agents.